Reflections beyond the screen an introduction to the meta-modern modality in Philippine cinema - Martin, Angelo Paolo T.
This study proposes the Meta-Modern Modality (MMM) as a theoretical framework in analyzing how Filipino filmmakers employ self-reflexive approaches in their films. The MMM framework examines three interconnected features: meta-reality, meta-narrative, and meta-commentary. The research centers on Ang Babae sa Septic Tank (Rivera, M., 2011) and Ekstra (Jeturian. J., 2013) as primary case studies that exemplify all three MMM features, supported by the analysis of nine comparator films. While these comparator films may not embody all MMM features. they demonstrate significant self-reflexive positioning that reflects aspects of the framework across three distinct periods from the 1971 to 2023. Through close reading and comparative historical analysis of selected films, the study traces how these MMM features evolved from coded resistance during political repression to explicit commentary in the digital age. The study's significance lies in developing a theoretical approach that reveals how films engage and critique the film industry across different social periods. The MMM framework provides new insights into how Filipino filmmakers maintains a self-reflexive positioning while adapting to changing conditions, demonstrating how films can function as creative works and vehicles for meaningful critical discourse.